Customer Data Search Application System at PT. Indonesian Islamic Bank Langsa Web-Based Branch - Novriadi Antonious Siagian; Pandi Barita Nauli Simangunsong; Muhammad Verdiansyah (INFOKUM, 2022)
This study aims to determine the role of Islamic banks in empowering MSMEs through murabaha financing in the city of Langsa, and to find out what obstacles Islamic banks face in providing financing. This study uses a qualitative descriptive method. The data sources are primary data and secondary data. Data collection techniques include observation, interviews and documentation. The results of this study indicate that Islamic banks have played a role in providing financing to micro, small and medium enterprises in the city of Bengkulu. Even though what is given by Islamic Banks is not a direct role because Islamic Banks only provide financing, not assisting directly.